Indonesian Primary School Science in Practices: The Development of an Instrument for Assessing Teachers' Perspectives on Curriculum Reform - Koto, Irwan; Treagust, David (SEAMEO RECSAM, 2011)
The primary purpose of this study was to describe the development of an instrument for assessing primary school teachers’ perspective on the curriculum reform in Indonesia. A two-phase study, with different respondents for each phase, involved 367 primary school teachers. The first phase, which utilized a 25 item closed and opened-ended questionnaire involving 107 teachers, was used to identify teachers’ perspectives on the curriculum reform. In the second phase of the study, which was used to pilot-test the instrument; items were based on the results of the first phase. The 47 items with a five-point Likert response scale were administered to 260 primary school teachers. Construct validity was confirmed through factor analysis that resulted in 36 items and 3 scales for the final instrument. Analyses of the data showed reliabilities of the three scales ranging from 0.78 to 0.62.